Highly hydrolysis-resistant polyester material and preparation method and application thereof

By blending the organic zirconium compound with polyester to form stable zirconium ester bonds and hydrophobic groups, the problem of polyester materials being easily hydrolyzed in humid environments or high temperature conditions is solved, and its hydrolysis resistance and service life are significantly improved.

CN118599270BActive Publication Date: 2025-02-21JIANGSU YIERMAN NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410684241.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-30
Publication Date
2025-02-21
Estimated Expiration
2044-05-30

AI Technical Summary

Technical Problem

Polyester materials are prone to hydrolysis reactions in humid environments or high temperature conditions, resulting in reduced mechanical properties and shortened service life.

Method used

Organozirconium compounds are blended with polyester to form stable zirconium ester bonds and hydrophobic groups to reduce the occurrence of hydrolysis reactions.

Benefits of technology

It significantly improves the hydrolysis resistance of polyester materials, maintains its mechanical properties and extends its service life, while avoiding adverse effects on the properties of polyester matrix.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of new materials, and specifically proposes a highly hydrolysis-resistant polyester material, a preparation method and an application thereof. By adding a preschool compound into the polyester material and co-extruding it with the polyester, the hydrolysis resistance of the polyester is significantly improved, and the polyester has adaptability for long-term use in a humid and hot environment. Using it for the backplane of a photovoltaic module can significantly increase the service life of the backplane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a highly hydrolysis-resistant polyester material and a preparation method and application thereof. Background Art

[0002] Polyester materials, especially polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), are widely used in fibers, films, packaging materials, engineering plastics and other fields due to their excellent mechanical properties, chemical stability and heat resistance. However, polyester materials are prone to hydrolysis in humid environments or high temperature conditions, resulting in the breakage of their molecular chains, which significantly reduces the mechanical properties and service life of the materials. This hydrolysis reaction is mainly caused by the reaction of the carboxyl group at the end of the polyester molecular chain with water molecules.

[0003] The hydrolysis reaction of polyester is an ester bond breaking reaction, which is particularly significant under high temperature and high humidity conditions. This reaction not only leads to a decrease in the mechanical strength and toughness of the material, but may also cause degradation of surface properties, such as color change and increased surface roughness. In addition, the by-products produced by the hydrolysis reaction (such as ethylene glycol and terephthalic acid) will further catalyze the hydrolysis process and accelerate the degradation of the material. These problems are particularly serious in some applications that require high environmental tolerance (such as outdoor fibers, protective films for electronic devices, and engineering plastics in the automotive industry), which seriously limits the application range and service life of polyester materials.

[0004] In order to improve the hydrolysis resistance of polyester materials, the prior art has proposed a variety of methods, including: introducing hydrolysis-resistant comonomers to improve the hydrolysis resistance of polyester, which often affects the crystallization and processing properties of polyester, and the selection and proportion of comonomers need to be precisely controlled; it also includes adding inorganic fillers to polyester to form a physical barrier to prevent water molecules from entering the polyester chain. Although this method can improve the hydrolysis resistance to a certain extent, the addition of fillers often affects the transparency and mechanical properties of the material. There is also a waterproof coating applied to the surface of the polyester material to prevent moisture from entering the interior of the polyester. Although this method is effective, the adhesion and durability of the coating are key issues, and this process will increase production costs and processing difficulty. Summary of the invention

[0005] In view of this, the present invention provides a highly hydrolysis-resistant polyester material.

[0006] The technical solution of the present invention is implemented as follows: the present invention provides a highly hydrolysis-resistant polyester material, the raw materials of which include polyester and an organic zirconium compound, and the molar percentage of the organic zirconium compound to the polyester is 0.05%-5%.

[0007] The organic zirconium compound is preferably an organic zirconium alkoxy compound, which can react with the carboxyl group at the end of the polyester molecular chain to form a stable zirconium ester bond, reduce the number of terminal carboxyl groups, and reduce the probability of hydrolysis reaction; secondly, the alkoxy group in the organic zirconium compound is large in size and will form a certain steric hindrance around the polyester chain. This steric hindrance effect further prevents water molecules from approaching and attacking the polyester chain; the hydrophobic group of the organic zirconium compound increases the hydrophobicity of the polyester material and reduces the adsorption and penetration of water on the surface of the material.

[0008] In some embodiments, the amount of the organic zirconium compound used is 0.1%-2% by mole of the polyester.

[0009] The above-mentioned implementation mode can effectively improve the hydrolysis resistance of polyester by limiting the dosage of the organic zirconium compound, while avoiding the influence on the performance of the polyester matrix caused by excessive dosage.

[0010] In some embodiments, the organic zirconium compound is one of tetra-n-butoxy zirconium, tetra-isopropoxy zirconium, and tetra-tert-butoxy zirconium.

[0011] In the above embodiment, three organic zirconium compounds that can be used for hydrolysis resistance modification of polyester are provided. Tetra-n-butoxy zirconium reacts with the carboxyl group at the end of the polyester molecular chain to form a zirconium ester bond. The zirconium ester bond is stable, which reduces the number of carboxyl groups at the end of the polyester and improves the stability of the polyester. At the same time, the byproducts generated by the reaction can form a shielding layer inside the polyester to prevent water molecules from further entering the polyester molecular chain; tetraisopropoxy zirconium can also react with the terminal carboxyl group to form an ester bond, and the steric hindrance of the isopropoxy group is large, which can provide a better shielding effect to prevent water molecules from entering the polyester molecular chain; tetra-tert-butoxy zirconium reacts with the terminal carboxyl group to form an ester bond, and the steric hindrance effect of the tert-butoxy group is significant, which can provide a better shielding effect, and its large group can passivate the activity of the polyester molecular chain.

[0012] In some embodiments, the polyester is one of polyethylene terephthalate and polybutylene terephthalate.

[0013] The second aspect of the present invention also provides a method for preparing a highly hydrolysis-resistant polyester material, comprising the following steps: blending polyester and an organic zirconium compound and adding the mixture into a twin-screw extruder, and extruding the mixture to obtain the highly hydrolysis-resistant polyester material.

[0014] In some embodiments, when the polyester is polyethylene terephthalate, the feeding end temperature of the twin-screw extruder is 230-250°C, the compression section temperature is 250-260°C, the metering section temperature is 260-280°C, and the head temperature is 260-280°C.

[0015] In some embodiments, when the polyester is polybutylene terephthalate, the feeding end temperature of the twin-screw extruder is 210-230°C, the compression section temperature is 230-240°C, the metering section temperature is 240-260°C, and the head temperature is 240-260°C.

[0016] During the extrusion process of the twin-screw extruder, gas discharge should be carried out appropriately to release the reaction by-products and avoid the by-products from affecting the quality of the polyester.

[0017] In a third aspect, the present invention also provides an application of the above-mentioned highly hydrolysis-resistant polyester material, which is used in the backplane of a photovoltaic module.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention adopts a simple co-extrusion method to modify the polyester material. The method is simple, low in cost, and easier to carry out industrial batch operation. The number of terminal carboxyl groups in the obtained polyester is greatly reduced, thereby improving the hydrolysis resistance of the polyester. Moreover, the reaction product of the organic zirconium compound can form a shielding layer inside the polyester to prevent the waterproof molecules from further entering the polyester molecular chain, further preventing the occurrence of the hydrolysis reaction. By reducing the molecular chain breakage caused by hydrolysis, the organic zirconium compound can maintain the molecular weight of the polyester material, maintain its good mechanical properties, and extend its service life. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0022] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0023] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0024] The present invention is further described below with reference to the embodiments.

[0025] Example 1

[0026] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was controlled at 250°C, the metering section temperature was controlled at 260°C, and the head temperature was controlled at 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets were mixed with 11 g (about 0.029 mol, accounting for 0.05 mol% of PET) of tetra-n-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0027] Example 2

[0028] The feed end temperature of the twin-screw extruder was controlled at 250°C, the compression section temperature was 260°C, the metering section temperature was 280°C, and the head temperature was 280°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets and 11 g (about 0.029 mol, accounting for 0.05 mol% of PET) of tetra-n-butoxyzirconium were mixed and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0029] Example 3

[0030] The feed end temperature of the twin-screw extruder was controlled at 210°C, the compression section temperature was 230°C, the metering section temperature was 240°C, and the head temperature was 240°C. 10 kg (about 45.5 mol) of polybutylene terephthalate (PBT) pellets were mixed with 7.5 g (about 0.023 mol, accounting for 0.05 mol% of PBT) of tetra-n-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0031] Example 4

[0032] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was 240°C, the metering section temperature was 260°C, and the head temperature was 260°C. 10 kg (about 45.5 mol) of polybutylene terephthalate (PBT) pellets were mixed with 7.5 g (about 0.023 mol, accounting for 0.05 mol% of PBT) of tetra-n-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0033] Example 5

[0034] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was 250°C, the metering section temperature was 260°C, and the head temperature was 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets and 1100 g (about 2.9 mol, accounting for 5 mol% of PET) of tetra-n-butoxyzirconium were mixed and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0035] Example 6

[0036] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was controlled at 250°C, the metering section temperature was controlled at 260°C, and the head temperature was controlled at 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets were mixed with 9.5 g (about 0.029 mol, accounting for 0.05 mol% of PET) of tetraisopropoxy zirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0037] Example 7

[0038] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was 250°C, the metering section temperature was 260°C, and the head temperature was 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets were mixed with 11 g (about 0.029 mol, accounting for 0.05 mol% of PET) of tetra-tert-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0039] Example 8

[0040] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was controlled at 250°C, the metering section temperature was controlled at 260°C, and the head temperature was controlled at 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets were mixed with 22 g (about 0.058 mol, accounting for 0.1 mol% of PET) of tetra-n-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0041] Example 9

[0042] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was controlled at 250°C, the metering section temperature was controlled at 260°C, and the head temperature was controlled at 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets were mixed with 440 g (about 1.16 mol, accounting for 2 mol% of PET) of tetra-n-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0043] Comparative Example 1

[0044] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was controlled at 250°C, the metering section temperature was controlled at 260°C, and the head temperature was controlled at 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets were mixed with 2.2 g (about 0.0058 mol, accounting for 0.01 mol% of PET) of tetra-n-butoxyzirconium and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0045] Comparative Example 2

[0046] The feed end temperature of the twin-screw extruder was controlled at 230°C, the compression section temperature was 250°C, the metering section temperature was 260°C, and the head temperature was 260°C. 10 kg (about 58.8 mol) of polyethylene terephthalate (PET) pellets and 2.2 kg (about 5.8 mol, accounting for 10 mol% of PET) of tetra-n-butoxyzirconium were mixed and added to the twin-screw extruder to obtain a highly hydrolysis-resistant polyester material.

[0047] The polyester materials prepared in the embodiment and the comparative example were respectively tested for hydrolysis resistance, and the testing method included: keeping the polyester material slices at a temperature of 121° C. and a humidity of 100% for 168 hours. After the test was completed, the viscosity characteristics of the polyester samples before and after hydrolysis were respectively detected, and the hydrolysis chain scission rate was calculated.

[0048] Where chain breaking rate = 0.244 (η a -1.47 -η b -1.47 ), where η a is the intrinsic viscosity of the sample after hydrolysis, η b is the intrinsic viscosity of the sample before hydrolysis. The performance data after the test are shown in the following table:

[0049] Grouping Terminal carboxyl group / mol / t Viscosity retention rate / % Hydrolysis chain scission rate / % Example 1 8 96.7 0.04 Example 2 7 96.6 0.04 Example 3 7 96.9 0.03 Example 4 7 96.8 0.03 Example 5 5 97.5 0.02 Example 6 7 96.8 0.03 Example 7 7 97.2 0.02 Example 8 6 97.1 0.02 Example 9 5 97.4 0.02 Comparative Example 1 12 79.2 0.21 Comparative Example 2 5 96.6 0.02 PET 22 73.5 0.25 PBT 21 74.7 0.25

[0050] In the above data, the test methods for terminal hydroxyl group, viscosity retention rate and hydrolysis chain scission rate are all carried out in accordance with the GB / T14190-2017 fiber-grade polyester chips (PET) test method.

[0051] The PET and PBT described in the above table are the raw materials of PET or PBT used in the above embodiments and comparative examples, and are intended to be used for blank case comparison.

[0052] It is not difficult to see from the above data that by adopting the preparation method of the present invention, the polyester is modified by co-extrusion using tetra-n-butoxy zirconium, tetra-isopropoxy zirconium and tetra-tert-butoxy zirconium as organic zirconium compounds, and the hydrolysis resistance of the polyester can be significantly improved. Among them, the hydrolysis resistance modification and improvement effect of tetra-tert-butoxy zirconium is the best. It is considered that after the addition of the organic zirconium compound, it reacts with the original terminal carboxyl group in the polyester, thereby playing a certain end-capping role. Some by-products of the reaction form a shielding layer, which further hinders the entry of water molecules, thereby significantly improving the hydrolysis resistance of the polyester.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly hydrolysis-resistant polyester material, characterized in that: The raw materials of the highly hydrolysis-resistant polyester material include polyester and an organic zirconium compound, wherein the molar percentage of the organic zirconium compound to the polyester is 0.05%-5%, the organic zirconium compound is one of tetra-n-butoxy zirconium, tetra-isopropoxy zirconium and tetra-tert-butoxy zirconium, and the polyester is one of polyethylene terephthalate and polybutylene terephthalate. The preparation method of the highly hydrolysis-resistant polyester material includes: blending the polyester and the organic zirconium compound and adding them into a twin-screw extruder to extrude the polyester material to obtain the highly hydrolysis-resistant polyester. When the polyester is polyethylene terephthalate, the feed end temperature of the twin-screw extruder is 230-250°C, the compression section temperature is 250-260°C, the metering section temperature is 260-280°C, and the head temperature is 260-280°C; when the polyester is polybutylene terephthalate, the feed end temperature of the twin-screw extruder is 210-230°C, the compression section temperature is 230-240°C, the metering section temperature is 240-260°C, and the head temperature is 240-260°C.

2. A highly hydrolysis-resistant polyester material as claimed in claim 1, characterized in that: The amount of the organic zirconium compound used is 0.1%-2% by mole of the polyester.

3. The use of the highly hydrolysis-resistant polyester material according to any one of claims 1 to 2, characterized in that: Used for photovoltaic module backplane.

Citation Information

Patent Citations

  • Hydrolysis-resistant polyester and preparation method thereof

    CN112724609A